SOSIALISASI PENGENALAN DATA BASE DALAM PROSES PEMBUATAN WEB - ARSI, ARKHOHUL; Dinar Ainun Nikmah; Egi Sugiana; Ihza Fauzan Rahadian; Mita Ratnasari; Mohamad Alaudin; Muhamad Eggie Saputra; Resta Rahastiani; Syifa Ilafiah; Muhamad Rosdiana (Jurnal Kreativitas Mahasiswa Informatika, 2023)
In today's digital age, the web has become one of the most important communication and information tools. In web creation, the use of databases becomes very important to store and manage the necessary data. The stages of the activity were carried out offline/directly on the spot on Friday, November 10, 2023, The socialization of database introduction aims to provide understanding to students of SMKN 8 Tangerang Regency about the importance of using databases in making webs. Students will be introduced to basic database concepts, such as tables, columns, and rows, as well as how to manage data in a database. In this socialization, students will be taught about the types of databases that are commonly used, such as MySQL, SQLserver, and MariaDB. They will also learn about the SQL language and queries used to access and manipulate data in databases. In addition, this socialization will also discuss the importance of data security in databases. Students will be given an understanding of the importance of protecting user data and maintaining the confidentiality of information stored in databases. It is hoped that with this socialization, students of SMKN 8 Tangerang Regency will have a better understanding of the use of databases in web creation. They will be able to manage data more efficiently and keep user data safe. This socialization is also expected to improve the quality of web creation produced by students of SMKN 8 Tangerang Regency.